The Growing Biorefinery of Agricultural Wastes: A Short Review - Fadzil, Nur Farhana; Othman, Siti Amira (Journal of Sustainable Natural Resources, 2021)
Living in the fast-developing world, wastes and residues from the various industrial sectors are increasing day by day in myriad quantity which strongly affected our health ecosystems and eventually the human community. Realizing this fact, there is demand for each agro-industrial sector for safe utilization of agro-materials through wastes recycling.  These residues constituent various valuable by-products can be exploited into biogas, bioenergy, biofuel, biocomposite and biomaterials which are applied into textiles industries, food safety and packaging, medical tool and many more. The demands of the present generation can be meet and fulfill without compromising the future generation sources. Hence, there is in-depth attention and studies of agro-industrial biorefinery as well as their recycling methods. This article presents a review on the classification of these residues, several refinery products of agro-industrial wastes and their challenges needed to overcome in the future.